Menjaga Kebalian: Jatidiri Orang Bali di Desa Tugumulyo Kabupaten Ogan Komering Ilir Provinsi Sumatera Selatan - Made Darme; Farida R. Wargadalem (Universitas Udayana, 2023)
The purpose of this study was to find out the process of entry and development of Hindus and to explain the identity of Balinese people in Tugumulyo Village, Lempuing District, Ogan Komering Ilir Regency, South Sumatra Province. The research methods used were historical that included heuristics, criticism, interpretation, historiography, and interviews. The study indicates that the presence of Hindus in Tugumulyo Village was caused by economic disparities in the previous transmigration area. The Hindu community in its religious activities is still the same in their application of the teachings of the Vedas. Balinese people with their Hindu religion, continue to maintain and develop self-concepts in a pluralistic society (Javanese, Komering, and others). This effort has paid off, it has been proven that the Balinese retain their identity, without putting tolerance aside. This article contributes to our understanding of harmonious life between people with different ethnic and religious backgrounds in a transmigration region in Indonesia.